Two new species of fresh water crab (Brachyura: Pseudothelphusidae) from Serranía de Los Paraguas, Cordillera Occidental, Colombia - Ramos-Tafur, Gabriel E. (2006)
Two new species of freshwater crabs of the genus Hypolobocera from Serranía de Los Paraguas, Cordillera Occidental, Colombia, are described. Hypolobocera solimani n. sp. is closely related to H. alata Campos 1989, but can be distinguished from it by smooth upper margin of third maxilliped merus, the size and shape of apex of first gonopod, and the internal lobe or papilla of spermatic channel, which is concave, raised, with ends with minute papillae or rounded tubercles. Hypolobocera triangula n. sp. is very similar to H. rotundilobata Rodríguez 1994, but differs from it by the shape and size of the lateral lobe, an oblique basal ridge of tubercles and by the apex of first gonopod. With the two new species, the total number of valid members of the genus Hypolobocera known from western Colombia or biogeographic Chocó is 20.